"Individuals, Institutions, processes" - "Shourie, Arun" (New Delhi, 1990)
A run Shourie, one of India's most respected journalists and political these and related questions in a series of learned and perceptive essays on the state of India today. Drawing upon his own experience and the years he has spent as an observer of Indian society, the author identifies and analyses the various ills that are undermining the country's institutions and the individuals who run them. He then shows how the wisdom of India's most eminent leaders-Gandhiji. Jayaprakash Narayan, J.B. Kripalani. Lokmanya Tilak, Lala Lajpat Rai-can still be profitably used by politicians. bureaucrats, trade unionists, journalists and others at the cutting edge of society to guide their actions. Taken together the essays in the book inform, educate and offer eminently practical suggestions to the responsible individual who wishes to a positive contribution to society.
Keywords: Politician